Can prosocial motivation harm entrepreneurs' subjective well-being? - Kibler, Ewald; Wincent, Joakim; Kautonen, Teemu; Cacciotti, Gabriella; Obschonka, Martin (Journal of Business Venturing, 2019)
Entrepreneurship research on prosocial motivation has outlined its positive impact on well-being, but still little is known about its power, which may have deleterious personal consequences under certain conditions. In this study, we ask whether prosocial motivation can harm entrepreneurs' subjective well-being when they run a commercial venture. Embedded within a contingency perspective informed by self-determination theory, we build on longitudinal survey data to explain the effect of prosocial motivation on entrepreneurs' overall life satisfaction. Our analysis demonstrates that prosocial motivation has a negative effect on entrepreneurs' life satisfaction due to increased levels of stress. However, our findings show that the negative effect of prosocial motivation dissipates when perceived autonomy at work is high compared to when it is low. Overall, our research raises questions on the role of prosocial motivation for entrepreneurs' subjective well-being and, in particular, discusses its potential “dark side” in the context of commercial entrepreneurship.